The Development of the Rempang Island Industrial Area from the Perspective of Abdul Majid Al-Najjar’s Maqashid Sharia - Fatkhurrozi, Tanto; Fageh, Achmad (Majapahit Journal of Islamic Finance and Management, 2024)
This study aims to critically analyze the development of the Rempang Island industrial area using Abdul Majid Al-Najjar’s Maqashid Sharia framework, with a focus on the principles of environmental preservation and the protection of human rights. This qualitative research adopts a library research approach, utilizing data from relevant documents, books, academic journals, and other references related to industrial development on Rempang Island. The findings reveal that the industrial development aligns partially with Al-Najjar’s maqashid sharia principles, particularly in terms of Hifzh Al-Biah min Al-Talaf (environmental preservation from destruction) and Hifzh Al-Biah min Al-Talawwuth (protection from pollution). However, in the context of Hifzh Al-Nafs (preservation of life), the forced relocation of local residents contradicts sharia objectives, as it threatens community welfare, disrupts livelihoods, and undermines social justice. Despite the government's provision of alternative locations for the affected communities, further evaluation is needed to ensure sustainable development that upholds both environmental and social justice in line with maqashid sharia principles.